Development of Test-Bed Controller for Powertrain of HEV - Peng Liu; Zhenhua Jin; Yuwei Hua; Lu Zhang (Energies, 2020)
The dynamic test-bed is a powerful tool for the powertrain integration and control strategy development of a hybrid electric vehicle (HEV). This paper focuses on developing a test-bed controller with driver simulation, road load simulation (RLS), and engine simulation. The main factors that influence the RLS accuracy are analyzed, especially inertia of test-bed and torque signal sampling frequency, and the RLS algorithm with penalty function based on a forward model is proposed. The engine model is developed and permanent magnet synchronous motor (PMSM) is adopted to realize engine start-up/stop, torque control, and inertia simulation. The simulation platform was built in MATLAB/Simulink to verify its accuracy. The simulation results present the developed RLS with a penalty function based on a forward model that can reduce the speed and torque error. The developed controller is applied to the single-axis parallel HEV test-bed. The experiment results show that the developed test-bed controller can precisely emulate the road load and improve the efficiency of the development of HEV powertrain.